In the court of public opinion: determining the criminal responsibility of autistic offenders - Liu, Weiyi (Nanyang Technological University, 2024)
Driven by the growing neurodiversity movement, the present study seeks to deepen society’s understanding of the challenges faced by the autistic community. One area pertinent to achieving an inclusive society is the criminal justice system. Autistic individuals often face challenges in their contact with the system, be it overrepresentation or unjust sentencing. The current investigation delves into the intricate dynamics of blame attribution processes in vignettes involving autistic offenders, aiming to highlight how types of crime and victim impact affects the public’s blame assignments. Through a multivariate analysis, significant differences were found between four vignettes detailing different offences (p = 0.003). Post-hoc analyses reveal some statistically significant comparisons. In general, significant comparisons show that compared to physical assault offences, sexual crimes resulting in emotional harm in particular are perceived to be the most intentional and blameworthy, resulting in higher legal culpability. It is also discovered that autistic physical assault offenders are perceived by the public to have higher levels of cognitive dysfunction compared to sexual offenders, despite both having the same descriptions with regards to their disability. The present investigation postulates that the moral judgments, influenced by the type of offence, affect blameworthiness first, colouring later judgments of blame mitigation.